Effect of Traditional Chinese Medicine on Inflammatory Mediators in Pediatric Asthma. (9th June 2016) - Du, Hui; Wang, Yonghong; Shi, Yumin; Yu, Jian; Sun, Wen; Zhang, Yiqun
Abstract : Objective . To observe the effects of empirical prescriptions of traditional Chinese medicine (TCM) on inflammatory mediators in pediatric asthma and to explore the underlying molecular mechanism in the treatment of asthma. Methods . A total of 182 children with asthma were randomly placed into either the TCM group (n = 97 ) or the salbutamol and montelukast (SM) group (n = 85 ). Patients in the TCM group were treated with a series of empirical prescriptions of TCM, while those in the SM group received salbutamol and montelukast. Both groups received their respective treatment for 12 weeks. There were 35 patients in TCM group and 34 patients in SM group providing venous blood. Real-time PCR was used to determine the mRNA expression levels of interleukin- (IL-) 10, IL-17, matrix metalloproteinase-9 (MMP-9), and transforming growth factor β 1 (TGF- β 1) in peripheral blood mononuclear cells before and after treatment. Enzyme-linked immunosorbent assay was used to measure the levels of IL-10, IL-17, MMP-9, and TGF- β 1 in peripheral blood before and after treatment. Results . The mRNA expression of TGF- β 1 in the SM group was downregulated (P = 0.00 ) after treatment. No significant differences were found between the TCM group and the SM group after treatment (P > 0.05 ). In the TCM group, the levels of IL-10, IL-17, and MMP-9 significantly decreased after treatment (P = 0.01, 0.04, and 0.03, resp.). In the SM group, IL-17, MMP-9, and TGF- β 1 levels significantly decreased after treatment (P = 0.00, 0.03, and 0.00, resp.). There was no significant difference between the two groups regarding the levels of IL-10, IL-17, TGF- β 1, and MMP-9 (P > 0.05 ). The difference of the level of IL-17 was negatively correlated with the change of C-ACT score in TCM group and SM group. Conclusion . TCM has a regulatory effect on the balance of some inflammatory mediators in pediatric asthma.